Words to Encourage Evangelization: A Comparison of Lexical Frequencies in the Writings of Pope Francis and Fr. Tomás Morales, SJ - María Martín-del Pozo (Ignatianum University Press, 2021)
Studying language through naturally-occurring data is easily feasible nowadays thanks to the use of concordancers. Using the software package AntConc by Laurence Anthony, the author approaches the linguistic style of Pope Francis in four of his apostolic exhortations. His lexical frequencies are compared to those of Venerable Fr. Tomás Morales, a Spanish Jesuit (1908-1994) who is considered a prophet of our time for anticipating the teachings of the Second Vatican Council twenty years beforehand. The two have several aspects in common, mainly in making laypeople aware of the universal call to sanctity and the missionary responsibility acquired in baptism. The results of the comparison show a similarity in the lexical choices. The article's conclusions and implications are considered in relation to the word in education and in evangelization.